2010
DOI: 10.1371/journal.pmed.1000324
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Plasmodium falciparum Malaria Transmission in Africa: A Model-Based Evaluation of Intervention Strategies

Abstract: BackgroundOver the past decade malaria intervention coverage has been scaled up across Africa. However, it remains unclear what overall reduction in transmission is achievable using currently available tools.Methods and FindingsWe developed an individual-based simulation model for Plasmodium falciparum transmission in an African context incorporating the three major vector species (Anopheles gambiae s.s., An. arabiensis, and An. funestus) with parameters obtained by fitting to parasite prevalence data from 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
658
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(681 citation statements)
references
References 90 publications
20
658
1
2
Order By: Relevance
“…Similar observations have been noted in areas formerly considered as high-transmission areas, such as Zambia [7] and Uganda [8]. A mathematical simulation of Plasmodium falciparum transmission in Africa suggested that only in areas with the lowest baseline level of transmission (<three infective bites per person per year) could malaria be eliminated through a combination of ITNs, IRS and case management with an artemisinin-based combination therapy (ACT) [9].…”
Section: Reviewsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar observations have been noted in areas formerly considered as high-transmission areas, such as Zambia [7] and Uganda [8]. A mathematical simulation of Plasmodium falciparum transmission in Africa suggested that only in areas with the lowest baseline level of transmission (<three infective bites per person per year) could malaria be eliminated through a combination of ITNs, IRS and case management with an artemisinin-based combination therapy (ACT) [9].…”
Section: Reviewsupporting
confidence: 56%
“…Review to be supplemented by additional strategies for malaria to be eliminated in most of sub-Saharan Africa, and the recognition that there is not yet a feasible technical strategy to eliminate P. vivax from Latin America and Asia, there is increased attention being paid to the human parasite reservoir [9,11]. The human parasite reservoir consists of all malaria infections in people in a given area, including symptomatic and asymptomatic infections, and both the sexual and asexual stages of the parasite (the special case of dormant liver stages of P. vivax and Plasmodium ovale will not be addressed in this review).…”
Section: Reviewmentioning
confidence: 99%
“…In resource poor settings, models, coupled with SA, may be used as a first step towards understanding control options. Whether by means of modelling behavioural interventions, biomedical interventions or through evaluation of social conditions and their impact on the disease system, infectious disease models have been used by decision-making bodies to explore and evaluate various policy options [48]. Where data are meager, SA can be used to identify key parameters upon which to focus limited data collection resources.…”
Section: Discussionmentioning
confidence: 99%
“…Some models indicate that LLIN and IRS combined would interrupt transmission in areas of moderate transmission 7,8 . Yet others suggest that the impacts could be antagonistic against the major African vectors: Anopheles gambiae s.s. 9 and A arabiensis 10 .…”
Section: Introductionmentioning
confidence: 99%